(3GdahGFO GdSfjI aj EYQGH CeKdI GdCLQhejIs - (3GdTGaYqj GdaQVqj, GdfLe, eMeO Hf jMji Hf Jbj GdOjf Hf YHGOI, (B1090 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bhd GdBLQhej GdcdGe gh GddaX GdeQcH GdeajO HGdhVY GdcdGe dg eYfjGf eYfi aj GddZI heYfi aj GdGUWdGM aeYfGg aj GddZI cdeG CaGO ef ETGQIs
(3BNQgG (B:s
(3dCfg ef GdCSeGA GdNeSI hgh eVGa hGdcGa VejQ eJUd aj eMd LQ HGdEVGaI hGddg JYGdi CYde JeJ EYQGH CeKdI GdCLQhejIs
(3aj BNQg fbhd hCOYjI hJhGQjN haGI dHYV GdCTNGU hfbhd aj GdfMh dGHf bGSes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 141s
(3eYLe GdeDdajf(B: 3 / 765s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs